PENGAWASAN DINAS PERINDUSTRIAN DAN PERDAGANGAN TERHADAP IZIN USAHA TOKO MODERN (IUTM) DI KOTA PEKANBARU TAHUN 2014 – 2015 (Studi Kasus: Swalayan dan Ritel) - Riyadi, Dicky Taufik; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The background of this study was the identification of the policies issued by the City of Pekanbaru in implementing the issuance of business licenses Modern Stores that are centered to Supermarkets and Retail as Indomaret and Alfamart in Pekanbaru. Then this study to analyze in depth related to the implementation of the supervision conducted by the City of Pekanbaru in this case carried out by the Department of Industry and Trade of the City of Pekanbaru. This research is descriptive. This study aimed to describe the real situation in the field accurately and systematically related research analysis and facts, as well as field observations and data or information obtained. Methods of data collection is carried out by means of observation, documentation, and interviews through field research.The results showed that the policies issued by the government in this case as Regional Regulation Pekanbaru No. 7 of 2000 on location permit, Government Regulation Number 112 of 2007 on Business Permit Modern Stores and later established by Regional Regulation Pekanbaru No. 9 of 2014 About Business License Modern Stores are rated not quite optimal in implementing the perturan. It is seen from some of the data provided by the Department of Industry and Trade of the City of Pekanbaru which in these data since the establishment of policies and regulations regarding business licenses Modern Store only 162 Modern Stores are owned Business Modern Stores (IUTM) with the distribution of 137 outlets Indomaret , 2 outlets Alfamart and 23 Supermarkets in the city of Pekanbaru. Thus the results of this study indicate that of the data that has been described in this study that the number of modern stores that have a business license Modern Store is not directly proportional to the number of modern stores in the city of Pekanbaru.Keywords: Controlling, Policy, Self-Service and Retail.